A New Dispersive Liquid-Liquid Microextraction Method for Preconcentration and Determination of Aluminum, Iron, Copper, and Lead in Real Water Samples by HPLC - Alpdogan, Guzin; Zor, Sule Dinc (AOAC INT, 2017)
In this study, dispersive liquid liquid microextraction coupled with HPLC with variable-wavelength detection was applied for the simultaneous determination of Al, Fe, Cu, and Pb in various water samples at trace levels. In the proposed method, all the system parameters in both the extraction and separation/determination steps, such as extraction and disperser solvent type and their volumes, complexing reagent concentration, salt addition, extraction and centrifugation times, and pH, were optimized to get not only high extraction efficiency but also lower LODs for the analytes. Hematoxylin was used as a complexing reagent, and carbon tetrachloride and methanol were chosen as the extraction and disperser solvents, respectively. Metal complexes were separated with a reversed-phase C18 column by isocratic elution, with methanol tetrahydrofuran water (20 + 12 + 68, v/v/v) as the mobile phase at a flow rate of 1.0 mL/min and detection at 575 nm. The accuracy of the method was checked by a Standard Reference Material of water (SRM 1643e), and the recovery values for the analytes were found in the range of 95.6-101.3%. Under the optimum conditions, the developed method was applied to tap water, bottled mineral water, lake water, and seawater for the accurate and sensitive determination of the analytes of interest.
Keywords: ATOMIC-ABSORPTION-SPECTROMETRY; CENTRAL COMPOSITE DESIGN; HEAVY-METAL IONS; SPECIATION ANALYSIS; TRACE AMOUNTS; CHROMATOGRAPHY; OPTIMIZATION; CO(II); UV; SPECTROPHOTOMETRY; Chemistry; Food Science & Technology